The Innovation of English Learning Resources Utilizing Interactive Games Aimed at Elementary School Students in Desa Pasar X - Thereza Angie Grifin; Rani Amelia Sihite; Sabrina Wandani Hutabarat; Mesra Sinambela; Chairos Valentino Sibarani (Asshika: Journal of English Language Teaching & Learning, 2024)
This study addresses the issue of insufficient utilization of effective learning media to enhance elementary school students' comprehension of the English language. The primary objective is to create interactive, game-based learning tools that facilitate a better understanding of English vocabulary among students. The research specifically targets elementary school students in Desa Pasar X Village, Kutalimbaru. Employing the Research and Development (R&D) methodology, the study follows the ADDIE model, which encompasses five phases: Analysis, Design, Development, Implementation, and Evaluation. Data collection methods included observation, as well as pre-test and post-test assessments to measure students' understanding. The implementation of interactive games, such as board games and plasticine activities, demonstrated significant effectiveness. The results from the post-test indicated a notable improvement in student comprehension, rising from 69.5% in the pre-test to 80.25%, thereby confirming that these media enhance students' retention and engagement in English learning. The successful development of interactive, game-based learning media has significantly bolstered students' grasp of English vocabulary, fostering a dynamic and enjoyable learning environment that encourages active participation and skill enhancement.